Effect of the Angle of the Crossed Fibres of a Fog Harvester on its Collection Efficiency. (July 2020) - Jia, Zhen; Zuo, Zhigang; Liu, Shuhong
Abstract: Although fog harvesting technology was firstly invented in the 1980s, the theoretical research is still in its infancy. To enhance the collection efficiency of fog harvester, lots of work have been done such as surface modification and 3D structure of the fibres of the fog harvester. In this study, based on observation of daily phenomenon, relationships between the angle of crossed fibres of the fog harvester between collection efficiency are discussed. Results show that as the angle of fibres changes, the effective collection rate per unit length of the fibre keeps unchanged, except near the maximum/minimum limits of the angle, where the collection rate drop significantly, caused by clogging according to the experimental observations. It is also found that the existence of fibre node will influence the collecting process of fog harvester, which can explain why harp-like fog harvester performs well in fog collection.